Identification of Lentil Varieties by Seed Protein Electrophoresis - KANCHAN SINGH; D. KHARE; S. RAO (Seed Research, 2026)
Twenty five varieties of lentil obtained from IIPR, Kanpur were analyzed for varietal identification through electrophoresis of seed protein. In all 15 bands were recorded with maximum relative mobility of 0.90. Presence or absence of any particular band helps in demarcation and identification of a variety. Similarity index was calculated to have an idea about evolutionary relationship among varieties in this experiment which varied from 53.3% to 93.3%.